The Role of International Law in Addressing Human Rights Violations in Armed Conflicts - Arjun Verma; Vikram Singh Rathore (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
International law plays a crucial role in addressing human rights violations during armed conflicts. This study examines the effectiveness of international legal frameworks, including the Geneva Conventions and the Rome Statute, in protecting civilians and prosecuting war crimes. By analyzing recent case studies from conflict zones, this research highlights the challenges of enforcing international law and suggests strategies for improving compliance among state and non-state actors.